Space charge limited conduction and determination of density of localised states in semiconductor cobalt doped TiO2 - Okutan, M; Yakuphanoğlu, Fahrettin; Bakan, HI; Inanir, F (Sage Publications Inc, 2006)
The space charge limited conduction (SCLC) mechanism in Co doped TiO2 has been investigated at different temperatures. At lower electric fields, ohmic behaviour is observed while at higher electric fields nonohmic behaviour is observed. The results obtained confirm the presence of SCLC in Co doped TiO2. The electronic parameters such as the position of the Fermi level above the valence band edge E-F, the density of states in valence band N-V and effective mass of holes m(h) were found as 12.32 meV, 1.26 x 10(15) m(-3) and 1.33 x 10(-7) m(e), respectively. The distribution of localised states in the forbidden band gap of the Co doped TiO2 was characterised by current-voltage measurements and the density of localised states near the Fermi level N(E-F) was found to be 2.11 x 10(17) eV(-1) m(-3).
Keywords: semiconductor; TiO2; space charged limited conduction; localised states